2018
DOI: 10.1155/2018/6862710
|View full text |Cite
|
Sign up to set email alerts
|

IR and UV/VIS Spectroscopic Characterization of the Higher Fullerene C76-D2 for Its Quantitative and Qualitative Determination

Abstract: The only stable isomer of the higher fullerene C76 of D2 symmetry was isolated from carbon soot by the new and advanced extraction and chromatographic methods and processes. Characterization of the isolated C76-D2 was performed by the IR(KBr) and UV/VIS method in the absorption mode. All of the experimentally observed infrared and electronic absorption bands are in excellent agreement with the theoretical calculations for this fullerene. The molar absorptivity ε and the integrated molar absorptivity Ψ of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(29 citation statements)
references
References 59 publications
(241 reference statements)
2
27
0
Order By: Relevance
“…All of the experimentally observed IR and UV/VIS maxima [20][21][22] and the general pattern of the obtained spectra of the isolated C 84 -D 2 :22 samples from our research, which showed similar properties [20,21,26,27,[36][37][38][39][40][41]43], are in excellent agreement with the theoretical predictions for this fullerene, with numerous possible absorption bands [20,21,26,27,[36][37][38][39][40][41]43,[54][55][56][57][58][59][60][61][62][63][64].…”
Section: Introductionsupporting
confidence: 87%
See 4 more Smart Citations
“…All of the experimentally observed IR and UV/VIS maxima [20][21][22] and the general pattern of the obtained spectra of the isolated C 84 -D 2 :22 samples from our research, which showed similar properties [20,21,26,27,[36][37][38][39][40][41]43], are in excellent agreement with the theoretical predictions for this fullerene, with numerous possible absorption bands [20,21,26,27,[36][37][38][39][40][41]43,[54][55][56][57][58][59][60][61][62][63][64].…”
Section: Introductionsupporting
confidence: 87%
“…The presence of the basic fullerenes was confirmed in various space environments, objects and their shells [1][2][3][4][5][6][7][8], as well as in the interstellar medium [9][10][11] and some resources on Earth [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], by means of IR and UV/VIS spectroscopy .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations